Lecture-based performance augmentation via game-based application ‘Kahoot!’ in Physical Education: a 5-week experimental study - Joseph Lobo (Physical Education of Students)
Background and Study Aim. Various published papers have already established the effectiveness of Kahoot! in bolstering students' academic performance through various games. However, there were few to no studies were conducted regarding its effectiveness in learning lecture-based concepts in Physical Education, most especially in the Higher Education setting. In this regard, this present study is aimed to assess the effectiveness of the said application via the Experimental approach.